Factors influencing purchase intention for recycled products: A comparative analysis of Germany and South Africa - Thomas Dobbelstein; Carina Lochner (Sustainable Development, 2023)
Due to an increasing demand, companies have started producing recycled products. However, little is known about the specific purchase behavior. Hence, this study analyses the factors influencing purchase intention for recycled products including differences related to different types of products and between Germany and South Africa. A quantitative study in Germany (n~=0.167em603) and South Africa (n~=0.167em692). shows that purchase intention is significantly higher in South Africa. The influencing factors (individual, product, and context related constructs) are the same in both countries, but they differ regarding their strength. Thus, the factor “attitude/environmental concern” has the strongest influence in South Africa, while it is “value/accessibility” in Germany. Furthermore, purchase intention for mobile phones is generally smaller than for t-shirts and toilet paper. Purchase intention for recycled t-shirts is significantly higher in South Africa than in Germany.
Keywords: 330; developed- and developing countries; influencing factors; product types; purchase intention; recycled products; sustainable development